THE ACHIEVEMENTS AND DRAWBACKS OF TRADITIONAL AND DISTANCE EDUCATION - Norinboyeva, Durdonaxon (Универсальная индексная библиотека Вестника педагогов нового Узбекистана, 2023)
During the pandemic, all educational institutions switched to distance learning. This article highlights the differences between distance education and traditional education, the pros and cons..